Angioplasty Outcomes in the Elderly Nepalese Patients: an eight years experience in Norvic International Hospital - Chirag, G; Rawat, B; Rajbhandari, S; Bhatta, Y; Jaiswal, JP; Vaidya, A (Nepalese Heart Journal, 2013)
Background The aim of the study is to evaluate and compare the outcomes of percutaneous transluminal coronary angioplasty (PTCA) between the elderly (>70 yrs) and the non-elderly (70 yrs and younger) Nepalese patients who had been admitted to Norvic International Hospital between early 2002 and April 2010. Methods Data of a total of 92 elderly and 604 non-elderly patients were retrospectively analyzed after they had been admitted in the Hospital for the interventional treatment of acute coronary syndrome. Results There were 64 (69.6%) male patients and 28 (30.4%) female patients in the elderly group. Elderly population had lesser smokers. Diabetic population was similar in both the age groups. The elderly patients slightly less success rate compared to the non-elderly (95.7% vs. 99.3%). There was no significant difference in bleeding complication and groin haematoma. In hospital death was 3.33% in elderly and 0.5% in non elderly. Conclusion Though the outcome in the elderly is poorer in comparison to the younger patients, it is an expected result when compared to even the biggest centres worldwide. DOI: http://dx.doi.org/10.3126/njh.v8i1.8334 Nepalese Heart Journal Vol.8(1) 2011 pp.27-29